Effects of Acute Stress on Thrombosis - Bentur, Ohad S.; Sarig, Galit; Brenner, Benjamin; Jacob, Giris (Seminars in Thrombosis and Hemostasis, 2018)
Stress, the nonspecific response to any demand for change, is an adaptive response of the human body to various stimulants. As such, stress-induced hypercoagulation may represent an adaptive response to bleeding. Numerous epidemiological studies have revealed that a correlation exists between stress and thrombotic risk and biochemically, links of the relationship between psychological stress and coagulation pathways have been made. The stress reaction is coupled with neurohormonal changes mediated mainly by the sympathetic neural system and the hypothalamic–pituitary–adrenal axis. Singling out the specific pathways affecting coagulation in this complex response is hampered by many confounders. The mediators of the stress reaction (neurotransmitters and hormones) can directly affect platelets and the coagulation cascade and indirectly affect hemostasis via changes in hemodynamics. In this review, the authors will delineate the distinct neurobiological mechanisms that govern the effects of stress on coagulation, and report their recent findings.
Keywords: stress; coagulation; sympathetic nervous system; cortisol